2012
DOI: 10.1021/es303471d
|View full text |Cite
|
Sign up to set email alerts
|

Novel and High Volume Use Flame Retardants in US Couches Reflective of the 2005 PentaBDE Phase Out

Abstract: California’s furniture flammability standard Technical Bulletin 117 (TB 117) is believed to be a major driver of chemical flame retardant (FR) use in residential furniture in the United States. With the phase-out of the polybrominated diphenyl ether (PBDE) FR mixture PentaBDE in 2005, alternative FRs are increasingly being used to meet TB 117; however, it was unclear which chemicals were being used and how frequently. To address this data gap, we collected and analyzed 102 samples of polyurethane foam from res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
312
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(327 citation statements)
references
References 22 publications
12
312
0
Order By: Relevance
“…While our UK study found no significant relationships between PFR concentrations in dust from cars, classrooms, homes, and offices and the presence of putative PFR sources in such UK microenvironments [11]; the same study did highlight elevated concentrations of TCIPP in house dust and suggested that this was likely attributable to extensive use of TCIPP in couch foam, as reported in the US [28]. This study explores this further, by comparing concentrations of TCIPP in Australian couch dust and from living rooms in which the couch was located; hypothesising that significantly elevated concentrations of TCIPP in couch compared to floor dust, combined with significant positive correlation between the two groups, would indicate couches to be a significant source.…”
Section: Introductionsupporting
confidence: 47%
“…While our UK study found no significant relationships between PFR concentrations in dust from cars, classrooms, homes, and offices and the presence of putative PFR sources in such UK microenvironments [11]; the same study did highlight elevated concentrations of TCIPP in house dust and suggested that this was likely attributable to extensive use of TCIPP in couch foam, as reported in the US [28]. This study explores this further, by comparing concentrations of TCIPP in Australian couch dust and from living rooms in which the couch was located; hypothesising that significantly elevated concentrations of TCIPP in couch compared to floor dust, combined with significant positive correlation between the two groups, would indicate couches to be a significant source.…”
Section: Introductionsupporting
confidence: 47%
“…The production volume of TCIPP was higher than that of TDCPP in the last few years; the worldwide production and usage volumes of TCIPP and TDCPP were 40,000 and 8,000 tons in 1997, respectively [7], while the use of TDCPP has increased significantly since the phase-out of PentaBDE [33]. Therefore, the present study documented the historical use patterns of TDCPP and TCIPP.…”
Section: Concentrations and Profiles Of Particle-bound Opfrsmentioning
confidence: 60%
“…Similar high proportions of TiBP (18-33 %) and TnBP (14-23 %) relative to ∑OPFRs have also been reported for indoor air in Sweden (Bergh et al 2011) and outdoor air in Norway (Green et al 2008) and the USA (Salamova et al 2014b). According to previous reports, over 98 % of TCPP was used as FR additive in building insulation materials and household products including PUF furniture (EC 2008b;Stapleton et al 2012), indicating that emissions from these materials may significantly contribute to OPFRs in indoor and outdoor air. The consumption of TCPP in the EU was over 40,000 t in 2000 and the production of TCPP over 46,000 t in the EU in 2008 (EC 2008b).…”
Section: Resultsmentioning
confidence: 99%